A History and Index of Alphabet Magazine - Brown, Douglas I. (My University, 1973)
The thesis traces the physical and editorial history of James Reaney's periodical Alphabet from 1960 to 1971, places the magazine within the larger construct of Reaney's own imaginative output and provides an index for the contributors and contents of the nineteen issues of the journal.
Keywords: English Language and Literature; English Language and Literature